Agroecology as a territory in dispute: between institutionality and social movements. Issue 3 (19th March 2018) - Giraldo, Omar Felipe; Rosset, Peter M.
Abstract : Agroecology is in fashion, and now constitutes a territory in dispute between social movements and institutionality. This new conjuncture offers a constellation of opportunities that social movements can avail themselves of to promote changes in the food system. Yet there is an enormous risk that agroecology will be co-opted, institutionalized, colonized and stripped of its political content. In this paper, we analyze this quandary in terms of political ecology: will agroecology end up as merely offering a few more tools for the toolbox of industrial agriculture, to fine tune an agribusiness system that is being restructured in the midst of a civilizational crisis or, alternatively, will it be strengthened as a politically mobilizing option for building alternatives to development? We interpret the contemporary dispute over agroecology through the lenses of contested material and immaterial territories, political ecology, and the first and second contradictions of capital.